2004
DOI: 10.1021/jm040790d
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of a Nitrogen Mustard Derivative Stabilized by Apo-neocarzinostatin

Abstract: Neocarzinostatin (NCS) is an antitumor antibiotic comprising a 1:1 protein-chromophore complex and exhibits cytotoxic action through DNA cleavage via H-abstraction. Cytotoxic activity resides with the chromophore 1 alone, while the protein (apoNCS) protects and transports labile 1. The naphthoate portion (2) of NCS chromophore (1) is important for binding to apoNCS and DNA intercalation. In this paper we describe our attempts to use apoNCS to improve the hydrolytic stability of novel bifunctional DNA alkylatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
33
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 28 publications
1
33
0
Order By: Relevance
“…Because of a technical problem, we lost the enriched sample after the structure determination and thus measured the relaxation data with a native protein at high concentration as described later. We confirmed that there is no concentration dependence for 13 C and 1 H chemical shift in the range of 2.5-8 mM by 13 C and 1 H-HSQC NMR spectra.…”
supporting
confidence: 74%
See 3 more Smart Citations
“…Because of a technical problem, we lost the enriched sample after the structure determination and thus measured the relaxation data with a native protein at high concentration as described later. We confirmed that there is no concentration dependence for 13 C and 1 H chemical shift in the range of 2.5-8 mM by 13 C and 1 H-HSQC NMR spectra.…”
supporting
confidence: 74%
“…However, there was no clarification between conformational ambiguity and the internal motion, which should be investigated by relaxation data in NMR. 13 C NMR relaxation studies were achieved for apo-NCS by Izadi-Pruneyre et al (24) and Mispelter et al (25), and yet there was no clear relation between the internal motion and the apo-NCS structural convergence (12,26). Here, we performed holo-NCS structural analysis with a combination of 13 C NMR methine relaxation experiments at natural abundance to investigate the internal motion of the loop and the chromophore-releasing mechanism.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…There has been recent interest in exploring the possibility of docking small synthetic molecules such as EtBr [32], naphthoate ester derivatives [33][34][35], and flavone-based ligand [36] in place of natural chromophore. Among the synthetic ligands, EtBr exhibits a relatively high binding constant (8.57 × 10 −7 M) [32] and has been frequently used to examine the binding properties of NCS mutants [37,38].…”
Section: Thermal Stability Of Ncs Protein With and Without Etbrmentioning
confidence: 99%